The conformation of beef animals as shown by measurements - Gardner, Edwin Chase (My University, 1904)
Introduction: "No detail is too small to be studied for truth." This is a well expressed thought for which we must give Stevenson credit, but we may bring it into our lives and make it our guide, with an assurance that such a course will always prove interesting. It is my opinion that no motto is so well suited to the student and judge of live stock as this one. Every variation has its significance, and this is especially true in regard to the conformation of beef animals. To the old and much experienced judge there are very few peculiarities in conformation that are not immediately evident, but with the beginner it is different. He feels the need of something definite to assist him in fixing a desirable type in mind. Often, also, in extremely close show contests a measurement might change the decision of the judges, or bring out some good quality before unperceived. It is with this idea in mind that I am about to give some measurements that I have taken, and to draw some conclusions from them. Lack of time and opportunity have considerably hindered the work so that I am compelled to confine myself to an examination of one breed of cattle, the Shorthorns. The individuals measured are some of the best out of forty-nine head sold at auction in Manhattan, and the best from the herd of T. K. Tomson and Sons of Lover, Kansas.
Citation: Gardner, Edwin Chase. The conformation of beef animals as shown by measurements. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Cattle; Measurements; Data Collection; Theses